Pengaruh Tingkat Pemberian Fermented Mother Liquor dalam Tepung Gaplek untuk Domba Betina Lokal yang sedang tumbuh - Retno Indrati; Gatot Murdjito; Harmadji . (Buletin Ilmu Makanan Ternak, 1990)
The experiment was conducted to investigate the effects of varios fermented mother liquor (FML) levels supplemented into cassava meal as ration for growing local female sheep.Parameterr measured involved feed consumption and average daily gains (ADG).The Animal feed composedof a basal ration of elephant grass supplemented with FML at levels of 0.0, 7.5, 15.0 dan 22.5 g, respestively. The ration was given individually amounting 240 g cassava meal and 1250 g elephant grass per animal.The results indicated that 15.0 g and 22.5 g FML supplementation increased cassava meal consumption (P<0.05) and ADG, decreased FCR and feed cost. The optimum ADG was 36.46 g that was obtained by the 22.5 g FML supplementation.